Perancangan sistem informasi akuntansi penjualan tunai pada konveksi Zunrock dengan vb.net metode RAD - Habibi, Ilham; Nurhakim, Hasbi; Rosalina, Resmi Ranti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The problem with sales cash receipt information system is a common problem that occurs in a company, the problems that arise occur because accumulation data with manual bookkeeping and the large number of cash receipts from sales which result in the data storage process being not well organized. The purpose of this study was to development accounting information system at Zunrock Apparel Convection. Researchers obtained data using interview techniques, literature study, and observation. The tools used in this survey are an interview form, a list of questions, and notes. In this research, the mechanism used system design stage. Method used is the RAD method. Testing cash receipts applications with Vb.Net program used black box testing method. Black box testing or also known as Behavioral Testing is a test carried out to observe input and output of the software without knowing code structure of the software. Based on results of design and test results of the zunrock apparel convection cash receipt application with Vb.Net program, it was concluded that use of the Rapid Application Development (RAD) method made cash receipt application design process more accurate and structured. This is because RAD method must be carried out sequentially based on predetermined forms.